1982
DOI: 10.1210/jcem-54-3-528
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary-Adrenocortical Function in Chronic Renal Failure: Blunted Suppression and Early Escape of Plasma Cortisol Levels after Intravenous Dexamethasone*

Abstract: The response to iv dexamehasone was studied in patients with chronic renal failure in whom resistance to suppression of plasma cortisol levels after oral steroid had been reported previously. One milligram of dexamethasone was given iv at 2300 h, and plasma cortisol levels were measured every 20 min between 0500-1000h in patients with renal failure, normal controls, and patients with pituitary-dependent Cushing's syndrome. Normal subjects showed a decrease in mean plasma cortisol levels to less than 3 microgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 10 publications
4
26
0
Order By: Relevance
“…Others [5]have suggested that intravenous dexamethasone may be more effective than oral dexamethasone in patients on hemodialysis. Some investigators [6, 7, 8]have suggested that a higher oral dose of dexamethasone be used for testing in renal failure patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Others [5]have suggested that intravenous dexamethasone may be more effective than oral dexamethasone in patients on hemodialysis. Some investigators [6, 7, 8]have suggested that a higher oral dose of dexamethasone be used for testing in renal failure patients.…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone suppression tests have been reported to be unchanged by some [3]and blunted by others [4, 5, 6, 7, 8]in patients on chronic hemodialysis. This lack of suppressibility has been attributed to various factors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite reduced excretion via the kidneys, baseline levels as well as diurnal vari ation and homeostatic regulation of cortisol appear near normal in most RDT patients [6,[95][96][97][98]. Measurements of adrenocortico tropic hormone are unreliable in uremia be cause of the accumulation of retained cross reacting substances.…”
Section: Hormones and Metabolic Abnormalitiesmentioning
confidence: 99%